Azithromycin Attenuates Pseudomonas-Induced Lung Inflammation by Targeting Bacterial Proteins Secreted in the Cultured Medium - Leal, Teresinha; Bergamini, Gabriella; Huaux, François; Panin, Nadtha; Noel, Sabrina; Dhooghe, Barbara; Haaf, Jeremy B.; Mauri, Pierluigi; Motta, Sara; Di Silvestre, Dario; Melotti, Paola; Sorio, Claudio (Frontiers in Immunology, 2016)
Background: Pseudomonas aeruginosa airway infections are a major cause of morbidity and mortality in patients with Cystic Fibrosis (CF). Azithromycin improves the related clinical outcomes but its mechanisms of action remain poorly understood. We tested the hypothesis that azithromycin down-regulates P. aeruginosa-induced pro-inflammatory responses by modifying release of bacterial proteins. Methods: We monitored inflammatory markers in lungs of CF mutant mice and their littermate controls in response to conditioned media (CM) collected from the reference P. aeruginosa PAO1 strain cultured in the presence or in the absence of azithromycin. A mass-spectrometry-based proteomic approach was applied to examine whether the macrolide elicits a differential release of bacterial proteins. Results: CM collected from azithromycin-untreated PAO1 cultures induced powerful pro-inflammatory neutrophil-dominated responses. Azithromycin attenuated the responses, mainly of macrophage chemoattractant protein-1, tumor necrosis factor-α and interferon-γ, in CF but not in wild-type mice. Proteomic analysis showed that azithromycin up-regulated an array of bacterial proteins including those associated with regulation of immune functions and with repair and resolution of inflammatory responses like the chaperone DnaK and the s-adenosylmethionine synthase, while it down-regulated the extracellular heme acquisition protein HasA and the catalytic enzyme lysylendopeptidase. Conclusions: Supernatants collected from cultures of the bacterial strain PAO1 represent a novel experimental model to trigger in vivo lung inflammatory responses that should be closer to those obtained with live bacteria, but without bacterial infection. Combined with a bactericidal effect, complex regulation of bacterial innate immune and metabolic factors released in the cultured medium by the action of the macrolide can contribute to its anti-inflammatory effects.